THE EFFECT OF ALL-TRANS RETINOIC ACID (ATRA) AND ZINC SULPHATE SUPPLEMENTATION ON PERIODONTITIS (KEMAS: Jurnal Kesehatan Masyarakat, 2015)
The study executed to know the effect of ATRA and Zn supplementations to periodontitis rat collagen treated with tetracycline.The experimental study with factorial design used 54 Wistar adult male rat. Periodontitis was resulted from porphyromonas gingivalis inoculation. Tetracycline 90 mg/kg and the supplementations were given for 7 days. Nine groups sample were randomly allocated. The independent variables were supplementation of ATRA 10; 5 mg/kg, Zn 2.5; 1 mg/kg, and their combinations. Dependent variable was collagen status i.e degradation and synthesis, consecutively measured by mRNA MMP-2 and mRNA P1CP, using reverse transcriptase polymerase chain reaction. Control was periodontitis group receiving tetracycline. T-test, ANOVA, Post Hoc Duncan and least significant differences (LSD) were used. High dose ATRA 10 mg/kg and Zn 2.5 mg/kg supplementations consecutivetly degraded (0.25 x of control) and increased collagen synthesis (4 x of control). High dose ATRA and Zn combined supplementation gave no effect to collagen degradation, but increased synthesis (3 x of control). The effect of high dose ATRA and Zn combined supplementation on collagen synthesis was the nearest to healthy condition.Penelitian ini bertujuan untuk mengetahui pengaruh suplementasi ATRA dan Zinc pada kolagen jaringan periodontium tikus periodontitis yang mendapat tetrasiklin. Studi eksperimental dengan desain faktorial dilakukan pada 54 tikus Wistar jantan dewasa. Periodontitis dihasilkan melalui inokulasi porphyromonas gingivalis. Tetrasiklin 90 mg/kg dan suplementasi diberikan selama 7 hari. Sembilan kelompok sampel terpilih secara alokasi acak. Variabel bebas adalah suplementasi ATRA 10; 5 mg/kg; Zn 2,5; 1 mg/kg; dan kombinasinya. Variabel tergantung adalah status kolagen meliputi degradasi dan sintesis, indikator mRNA MMP-2 dan mRNA P1CP, terukur dengan reverse transcriptase polymerizing chain reaction. Kontrol adalah kelompok periodontitis dan mendapat tetrasiklin. Analisis data menggunakan uji t, ANOVA, Post Hoc Duncan, dan LSD.  Suplementasi dosis tinggi ATRA 10 mg/kg dan Zn 2,5 mg/kg berturut-turut mendegradasi (0,25 x kontrol) dan meningkatkan sintesis kolagen (4 x kontrol). Kombinasi suplementasi dosis tinggi ATRA dan Zn tidak berefek pada degradasi kolagen, tetapi meningkatkan sintesisnya (3 x kontrol). Suplementasi kombinasi dosis tinggi ATRA dan Zn memberikan sintesis kolagen paling dekat dengan keadaan sehat.